2022
DOI: 10.30574/gscbps.2022.19.2.0178
|View full text |Cite
|
Sign up to set email alerts
|

Natural sources as promising future anticancer therapies - A review

Abstract: Cancer is the second leading cause of death worldwide. The alternative natural therapies are required as they considered to have less toxic side effects compared to current chemotherapy. In the current review Web Science, PubMed, Scopus and Science Direct, were searched to provide information about medicinal plants that have shown anticancer activity against various forms of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 291 publications
0
2
0
Order By: Relevance
“…Pharmacological investigations have demonstrated that O. spinosa exhibits noteworthy hepatoprotective and antitumor properties [250], and may be considered a potential therapeutic agent for the management of urinary tract infections and bladder stones [247].…”
Section: Ononis Spinosa L Legume Family -Fabaceaementioning
confidence: 99%
“…Pharmacological investigations have demonstrated that O. spinosa exhibits noteworthy hepatoprotective and antitumor properties [250], and may be considered a potential therapeutic agent for the management of urinary tract infections and bladder stones [247].…”
Section: Ononis Spinosa L Legume Family -Fabaceaementioning
confidence: 99%
“…Pharmacological investigations have demonstrated that O. spinosa exhibits noteworthy hepatoprotective and antitumor properties [ 225 ], and may be considered a potential therapeutic agent for treating urinary tract infections and bladder stones [ 222 ].…”
Section: Introductionmentioning
confidence: 99%